2020
DOI: 10.1101/2020.08.13.250001
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fibroblast Mechanotransduction Network Predicts Targets for Mechano-Adaptive Infarct Therapies

Abstract: Regional control of fibrosis after myocardial infarction is critical for maintaining structural integrity in the infarct while preventing collagen accumulation in non-infarcted areas. Cardiac fibroblasts modulate matrix turnover in response to biochemical and biomechanical cues, but the complex interactions between signaling pathways confounds efforts to develop therapies for regional scar formation. Here, we employed a logic-based ordinary differential equation model of fibroblast mechano-chemo signal transdu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…Upon filtering the initial gene regulatory network for interactions contained in either database, the resulting network was filtered further for interactions containing TFs or fibrosis-related target genes in myofibroblasts. Lists of TFs and target genes were derived using our curated network model of myofibroblast signaling ( 59 ), which contains 11 primary TFs and 20 target genes coding for ECM-related proteins. For TFs that consist of several subunits (e.g., activator protein 1 [AP1] complex), both constituent genes were included for filtering.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon filtering the initial gene regulatory network for interactions contained in either database, the resulting network was filtered further for interactions containing TFs or fibrosis-related target genes in myofibroblasts. Lists of TFs and target genes were derived using our curated network model of myofibroblast signaling ( 59 ), which contains 11 primary TFs and 20 target genes coding for ECM-related proteins. For TFs that consist of several subunits (e.g., activator protein 1 [AP1] complex), both constituent genes were included for filtering.…”
Section: Methodsmentioning
confidence: 99%
“…We combined the final transcriptional network with our previous myofibroblast signaling network describing intracellular mechanotransduction and chemotransduction ( 59 ) to form a composite network capable of predicting fibrosis-related protein expression in response to mechanical and biochemical stimuli. New TFs (model nodes) and/or transcriptional reactions (edges) were added to the cell signaling topology if they were not redundant to the original transcriptional reactions described by the signaling network.…”
Section: Methodsmentioning
confidence: 99%
“…To help identify potential signaling connections between mechanical tension and regional fibrosis, we adapted a previously published computational model of cardiac fibroblast (CF) signaling pathways. 21 , 22 This model captured the activity levels of 109 signaling molecules and 174 reactions connecting biochemical and mechanical input stimuli (mechanical tension, transforming growth factor beta 1, angiotensin II, interleuken 1, interleuken 6, plateletā€derived growth factor, tumor necrosis factor alpha, endothelin 1, norepinephrine, and natriuretic peptide) to predict fibrosisā€related outputs (collagen I, collagen III, fibronectin, periostin, Ī±ā€SMA, matrix metalloproteinases, tissue inhibitors of metalloproteinases, and others). In the present study, we integrated an additional 27 new signaling molecules and 50 new network reactions related to cilia signaling that were manually curated from existing literature reports (Tables S2 and S3 ).…”
Section: Methodsmentioning
confidence: 99%
“… 22 In our past modeling studies, this model has successfully predicted ā‰ˆ82% (96/118) of previously reported signaling responses by CFs under a wide variety of biomechanical and biochemical stimulation conditions. 21 , 22 Importantly, these validation agreements are based on >100 independent experimental studies, not including the ā‰ˆ300 experimental studies used to build the model. In the current study, we investigated the connection between mechanical tension, cilia signaling, and downstream collagen production.…”
Section: Methodsmentioning
confidence: 99%
“…One way to hasten this investigation could be through the use of sex-specific computational disease models. Existing disease models such as the signaling network model of cardiac fibroblasts' response to mechano-chemo signaling could be improved through the incorporation of biological sex and hormone pathways [37,38]. Large-scale sex-specific network modeling could greatly accelerate the pace and reduce the costs of identifying important interactions involved in the regulation of fibrosis rather than trial and error experiments alone.…”
Section: Discussionmentioning
confidence: 99%